Performance comparison of optimization techniques in EHS system using sliding mode controller. Issue 1 (April 2020) - Chai, M S; Ghazali, R; Chong, S H; Soon, C C; Too, J; Sam, Y M
Abstract: Electro-Hydraulic Servo (EHS) system is a well-known nonlinear system in various types of industries due to its outstanding characteristics over other actuators. Despite its wide applications in industries, this system also suffering from nonlinearities and parameter uncertainties. Sliding Mode Controller (SMC) has been proven by many researchers to be effective in positioning control of the nonlinear system. However, SMC controller parameters must be tuned in appropriate ways to control the EHS system. In this research, an SMC strategy which combines with an enhanced PSO called Multi-Objective Particle Swarm Optimization (MOPSO) is proposed in positioning control of the EHS system. The conventional PSO is design as well for comparison purpose. The output performance is analysed and verified using different performance indexes such as rise time, settling time, overshoot percentage, and root mean square error. The results show that the MOPSO is better in tuning the controller parameters.